Analyses of Lipid A Diversity in Gram-Negative Intestinal Bacteria Using Liquid Chromatography–Quadrupole Time-of-Flight Mass Spectrometry - Nobuyuki Okahashi; Masahiro Ueda; Fumio Matsuda; Makoto Arita (Metabolites, 2021)
Lipid A is a characteristic molecule of Gram-negative bacteria that elicits an immune response in mammalian cells. The presence of structurally diverse lipid A types in the human gut bacteria has been suggested before, and this appears associated with the immune response. However, lipid A structures and their quantitative heterogeneity have not been well characterized. In this study, a method of analysis for lipid A using liquid chromatography–quadrupole time-of-flight mass spectrometry (LC-QTOF/MS) was developed and applied to the analyses of Escherichia coli and Bacteroidetes strains. In general, phosphate compounds adsorb on stainless-steel piping and cause peak tailing, but the use of an ammonia-containing alkaline solvent produced sharp lipid A peaks with high sensitivity. The method was applied to E. coli strains, and revealed the accumulation of lipid A with abnormal acyl side chains in knockout strains as well as known diphosphoryl hexa-acylated lipid A in a wild-type strain. The analysis of nine representative strains of Bacteroidetes showed the presence of monophosphoryl penta-acylated lipid A characterized by a highly heterogeneous main acyl chain length. Comparison of the structures and amounts of lipid A among the strains suggested a relationship between lipid A profiles and the phylogenetic classification of the strains.